Propuesta de mejora del proceso de producción de biogás en Jerusalén Cundinamarca (2018)
The generation of energy from sources considered clean is currently booming, because the consumption and exploitation of fossil fuels is one of the main causes of pollution facing our planet Earth, therefore the This work is focused on establishing alternatives for improvement to the anaerobic biodigestion system, located in certain farms managed by the families of the hamlet, approximately 7 km from the municipality of Jerusalem. This arose as part of a pilot plan of the Regional Autonomous Corporation to make Jerusalem the first eco sustainable municipality in Cundinamarca, generating biomass of better quality through analysis in the increase mainly of the methane content in the gas obtained with the aim of creating clean renewable energies and in this way contribute to the reduction of environmental pollution and eventually economic costs.